AB0036C IMMUNOPHENOTYPIC CHARACTERIZATION OF T-CELL IN PATIENTS WITH RHEUMATOID ARTHRITIS TREATED WITH GOLIMUMAB. (June 2019) - Lopez-Mayorga, María-Mercedes; Barbosa-Cobos, Rosa-Elda; Moreno-Eutimio, Mario Adán; Becerril Mendoza, Lizbeth Teresa; Henríquez, Pedro Rodríguez; Lugo, Gustavo; Maya-Piña, Lucía-Verónica; Hernández-Jaimes, Olivia; Moreno, José
Abstract : Background: Golimumab is a human anti-TNF monoclonal antibody that has shown efficacy in RA. In the RA pathophysiology, the elevation of TNF modulates the cellular immune response, which leads to a sustained activation of T-cell response; however, it is unknown whether anti-TNF interferes with the immunophenotype of T-cell. Objectives: To evaluate activation (CD25, CD69) and exhausted (PD-1, TIM-3, LAG-3, CTLA-4) markers of T-cells in RA patients treated with Golimumab. Methods: We included 14 patients with RA diagnosis (Criteria ACR/EULAR 2010), with moderate to severe activity; 11 non-responders to synthetic DMARDs (NR-DMARDs) and 3 responders to synthetic DMARDs with pharmacological toxicity (R-DMARDs). All patients were treated with Golimumab during 24 weeks. The questionnaire SF-36, DAS28-CRP, power Doppler signal and expression of CD25, CD69, PD-1, TIM-3, LAG-3 and CTLA-4, in T-cell were evaluated at 0 and 24 weeks. Results: Clinical variables evaluated in patients with Rheumatoid Arthritis are shown in tables 1 and 2. The frequency of LAG-3+ on CD4+ T-cells increased after 24 weeks of treatment with Golimumab (p = 0.013) (figure 1 ). The expression of LAG-3 in CD4+ T-cells (r = -0.586, p = 0.028) (Figure 2 ) and CD8+ T-cells (r = -0.617, p = 0.019) (Figure 3 ) inversely correlated with DAS28-CRP after treatment. At the beginning of treatment NR-DMARDs patients showed higher expression of CD25 in CD8+ T-cells and lower expression of TIM-3 in CD4+ and CD8+ T-cells with respect to R-DMARDs. After 24 weeks of treatment, a lower frequency of CD69+ and LAG-3+ T-cells was found and increased of CD25+ T-cells compared to R-DMARDs. Conclusion: Golimumab treatment increased the expression of LAG-3 in T-cells, suggesting a negative regulator of antigen presentation of T-cells. References: [1] Tahir Z, Kavanaugh A. The role of golimumab in inflammatory arthritis. A review of the evidence. Ther Adv Musculoskel Dis2018;9:181–194. [2] Cuda C, Pope R, Perlman H. The inflammatory role of phagocyte apoptotic pathways in rheumatic diseases. Nat rev Rheumatol2016;12: 543-555. [3] Wherry E, Kurachi M. Molecular and celular insights into T cell exhaustion. Nat rev Inmunol 2015;15: 486-496. [4] Burmester G, Feist E, Dörner T. Emerging cell and cytokine targets in rheumatoid arthritis. Nat rev Inmunol2013;15:1-10. [5] McKinney E, Lee J, Jayne D, Lyons P. T-cell exhaustion, co-stimulation and clinical outcome in autoimmunity and infection. Nat rev Inmunol2015;523: 612-616. Disclosure of Interests: None declared